Predictors of Mortality in Hospitalized HIV/AIDS Patients - Puspitasari, Estie; Yunihastuti, Evy; Rengganis, Iris; Rumende, Cleopas Martin (Jurnal Penyakit Dalam Indonesia, 2016)
Introduction. Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) is a big problem that threatening in Indonesia and many countries in the world. The knowledge on the characteristics and prediction of outcome were important for patients management. There are no studies on the predictors of mortality in Indonesia. Methods. We performed a retrospective cohort study among hospitalized patients with HIV/AIDS in Cipto Mangunkusumo Hospital between 2011-2013. Datas on clinical, laboratory measurement, outcome (mortality) and causes of death during hospitalization were gathered from medical records. Bivariate analysis using Chi- Square test were used to evaluate seven prognostic factors (male sex, not came from referral hospital, never received/failed to continue antiretroviral therapy (ART), clinical WHO stage 4, hemoglobin level /dL, eGFR level /min/1.73 m2 and CD4+ count ≤200 cell/µL). Multivariate logistic regression analysis was performed to identify independent predictors of mortality. Results. Among 606 hospitalized HIV/AIDS patients (median age 32 years; 64.2% males), 122 (20.1%) were newly diagnosed with HIV infection during the hospitalization and 251 (41.5%) had previously received ART. Median length of stay was 11 (range 2 to 75) days. There were 425 (70.1%) patients being hospitalized due to opportunistic infection. In-hospital mortality rate was 23.4% with majority (92.3%) due to AIDS related illnesses. The independent predictors of mortality in multivariate analysis were clinical WHO stage 4 (OR=6.440; 95% CI 3.701-11.203), hemoglobin level /dL (OR=1.542; 95% CI 1.015- 2.343) and eGFR level /min/1.73 m2 (OR=3.414; 95% CI 1.821-6.402). Conclusions. In-hospital mortality rate was 23.4%. Clinical WHO stage 4, hemoglobin level /dL and eGFR level / min/1.73 m2 were the independent predictors of in-hospital mortality among hospitalized patients with HIV/AIDS.